A Thematic Content Analysis Concerning the Emotional Message Repertory of the TV Commercials of the Products Directed at the Young Target Audience - Bati, Ugur; Atici, Bunyamin (Online Journal Communication & Media Technologies-Ojcmt, 2016)
The purpose of this study is to reveal the emotional message repertory in the television commercials directed at the young target audience. A content analysis is realized in the coverage of the study. The content analysis is used in the study. Total 2482 commercial spots, which are broadcasted in the prime time hours in 4 different national channels are recorded. The number of the commercials addressing to the young target audience between them became 1193. It is seen in the study that the commercials directed at the young target audience realized in 9 different categories. 10 different thematic categories are put forward directed at the young people in these 9 categories. The distribution of the mentioned categories to the channels is performed. In addition to this, most repeated 10 commercials are determined in all of the commercials and young commercials and the message contents of these commercials are examined. It is determined that the maximum messages directed at the young people among all of the commercials are in the food and beverage category with 425 single commercials. When it is looked at the thematic distribution, the messages concerning the difference took part in the first place among all of the commercials with 390 commercials.
Keywords: Commercial; Television Commercials; Young products; Emotional Commercial Message Strategies; Content Analysis